Effectiveness of Mind-Body Interventions Delivered by Nurses in Improving Psychological Well-being and Surgical Recovery: A Meta-Analysis - Rifki Sakinah Nompo; Fatimah Fatimah; Josepha Mariana Tamaela; Fathia Fakhri Inayati Said (Archives of The Medicine and Case Reports, 2025)
Surgical patients often experience psychological distress that can hinder their recovery. Mind-body interventions (MBIs) delivered by nurses, such as guided imagery and mindfulness exercises, may improve psychological well-being and surgical recovery. This meta-analysis examined the effectiveness of nurse-delivered MBIs on adult surgical patients. A systematic search of PubMed, CINAHL, PsycINFO, and Cochrane Library databases was conducted from January 2013 to November 2024. Randomized controlled trials (RCTs) examining the effects of nurse-delivered MBIs on adult surgical patients were included. Primary outcomes were anxiety, depression, and pain. Secondary outcomes included length of hospital stay, postoperative complications, and medication usage. Random-effects models were used to calculate pooled effect sizes (Hedges' g). Six RCTs met the inclusion criteria, comprising 785 participants. Meta-analysis revealed that nurse-delivered MBIs significantly reduced anxiety (g = -4.09, 95% CI [-6.25, -1.93], p = 0.0002) and depression (g = -3.40, 95% CI [-4.96, -1.85], p < 0.00001) compared to standard care. Significant reductions in postoperative pain (g = -1.77, 95% CI [-2.10, -1.44], p < 0.00001) were also observed. No significant differences were found for length of hospital stay or postoperative complications. In conclusion, nurse-delivered MBIs effectively improve psychological well-being and reduce postoperative pain in adult surgical patients, supporting their integration into routine surgical care.